An expression is shown/

4(34x+3x−2)−2(3x2+1+3x)

Rewrite an equivalent expression with the fewest terms possible

(3 points)

5 answers

To simplify the expression \( 4(34x + 3x - 2) - 2(3x^2 + 1 + 3x) \), we'll follow the steps of distributing and combining like terms.

  1. Distribute the \(4\) and \(-2\):

\[ 4(34x) + 4(3x) + 4(-2) - 2(3x^2) - 2(1) - 2(3x) \]

Simplifying that gives us:

\[ 136x + 12x - 8 - 6x^2 - 2 - 6x \]

  1. Now, combine like terms:
  • Combine the \(x\) terms: \[ 136x + 12x - 6x = 142x \]

  • The constant terms: \[ -8 - 2 = -10 \]

Putting it all together, we have:

\[ -6x^2 + 142x - 10 \]

So the final simplified expression is:

\[ -6x^2 + 142x - 10 \]

This is the equivalent expression with the fewest terms possible.

An equation is shown.

y−5 = −3(x+6)
(2 points)
The equation rewritten in slope-intercept form is
.

The point
is on the graph of the line.

To rewrite the equation \( y - 5 = -3(x + 6) \) in slope-intercept form (which is \( y = mx + b \) where \( m \) is the slope and \( b \) is the y-intercept), follow these steps:

  1. Distribute the \(-3\) on the right-hand side:

    \[ y - 5 = -3x - 18 \]

  2. Add \(5\) to both sides to isolate \(y\):

    \[ y = -3x - 18 + 5 \]

    \[ y = -3x - 13 \]

So, the equation rewritten in slope-intercept form is:

\[ y = -3x - 13 \]

Next, to determine a point that is on the graph of the line, we can choose any \(x\) value and substitute it into the equation to find the corresponding \(y\) value.

Let's choose \(x = 0\):

\[ y = -3(0) - 13 = -13 \]

Thus, the point \((0, -13)\) is on the graph of the line.

Final Results:

  • The equation in slope-intercept form is: \(y = -3x - 13\)
  • A point on the graph of the line is: \((0, -13)\)
What is the slope-intercept form of the linear equation 5x+3y=9
?(1 point)
Responses

y = −53x+3
y = −53x+3

y = 53x+3
y = 53x+3

y = −53x+9
y = −53x+9

y = −5x+3
y = −5x+3

y = 53x−3

To convert the equation \(5x + 3y = 9\) to slope-intercept form \(y = mx + b\), we need to isolate \(y\).

Here are the steps:

  1. Subtract \(5x\) from both sides: \[ 3y = -5x + 9 \]

  2. Divide every term by \(3\) to solve for \(y\): \[ y = -\frac{5}{3}x + 3 \]

So the slope-intercept form of the equation is:

\[ y = -\frac{5}{3}x + 3 \]

From the given options, the correct response is:

y = −\(\frac{5}{3}\)x + 3.

Similar Questions
  1. An expression is shown/4(34x+3x−2)−2(3x2+1+3x) Rewrite an equivalent expression with the fewest terms possible (3 points) x2
    1. answers icon 1 answer
  2. An expression is shown/4(34x+3x−2)−2(3x2+1+3x) Rewrite an equivalent expression with the fewest terms possible (3 points) x2
    1. answers icon 11 answers
  3. An expression is shown.(-29 - 10x^2 + 12x) + 3x(5x - 4) Rewrite an equivalent expression with the fewest terms possible.
    1. answers icon 1 answer
  4. An expression is shown/4(3/4x+3x−2)−2(3x^2+1+3x) Rewrite an equivalent expression with the fewest terms possible. __x^2 +
    1. answers icon 1 answer
more similar questions